2009
DOI: 10.1111/j.1742-4658.2009.07109.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel ATP‐binding cassette transporter is responsible for resistance to viologen herbicides in the cyanobacterium Synechocystis sp. PCC 6803

Abstract: The charged quaternary ammonium compounds – methyl, ethyl and benzyl viologens – generate reactive oxygen species in photosynthetic cells. Three independent methyl viologen‐resistant spontaneous mutants of Synechocystis sp. PCC 6803 were identified, in which the conserved R115 residue of the Slr1174 protein was replaced with G115, L115 and C115. The Slr1174 protein of the DUF990 family is related to the permease subunit of an ABC‐2‐type transporter and its R115 mutation was found to be solely responsible for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…Furthermore, glyphosate entry into the cell can be markedly inhibited by vanadate pretreatment. These characteristics are similar to those of ATP-binding cassette transporters in plants (Hetherington et al, 1998;Rea, 2007;Verrier et al, 2008;Prosecka et al, 2009;Conte and Lloyd, 2011) and mammalian cells (van de Ven et al, 2009;Ernst et al, 2010).…”
supporting
confidence: 59%
“…Furthermore, glyphosate entry into the cell can be markedly inhibited by vanadate pretreatment. These characteristics are similar to those of ATP-binding cassette transporters in plants (Hetherington et al, 1998;Rea, 2007;Verrier et al, 2008;Prosecka et al, 2009;Conte and Lloyd, 2011) and mammalian cells (van de Ven et al, 2009;Ernst et al, 2010).…”
supporting
confidence: 59%
“…In addition, the transcription level of BN_1434-1433 encoding an ABC-2 type transporter was respectively 3.59-and 4.73-fold up-regulated under bile stress conditions. Among ABC-2 type transporters, Drr and Evr have been reported to pump toxic compounds, such as daunorubicin and doxorubicin in Streptomyces lucretius (49) and viologen in Synechocystis (50). These results suggested that this transporter may possibly perform similar function of bile exclusion in BBMN68 in response to bile stress.…”
Section: Global Transcriptomic and Proteomic Analysis Of The Bile Strmentioning
confidence: 93%
“…Huang, and S. Powles, unpublished data). In bacteria, several multidrug transporter genes have been isolated that confer paraquat resistance by paraquat extrusion or sequestration (e.g., 147,186). Recently, two differentially expressed EST sequences were identified in paraquat-resistant C. canadensis.…”
Section: Paraquat Resistance By Restricted Paraquat Translocationmentioning
confidence: 99%